Diversity of Ganoderma pathogen in Pontianak, West Kalimantan: Characteristics, virulence and ability to infect Acacia mangium seedlings - ROSA SURYANTINI; REINE SUCI WULANDARI (Society for Indonesian Biodiversity, 2018)
Suryantini R, Wulandari RS. 2018. Diversity of Ganoderma pathogen in Pontianak, West Kalimantan: Characteristics, virulence and ability to infect Acacia mangium seedlings. Biodiversitas 19: 465-471. The study aimed to determine morphological characteristics and virulence of Ganoderma isolates. The method that was used: isolation and characterization isolate from Acacia mangium, palm oil (Elaeis guineensis) and rubber (Hevea brasiliensis); inoculation of isolate in A. mangium; its influence to seedling dry weight. Results showed that isolated from A. mangium is G. lucidum, from palm oil is G. boninense and isolated from rubber plant is G. applanatum. Symptoms were observed within 3 months after inoculation. Symptoms began with chlorosis, necrosis and then seedling death. The G. lucidum is of highest virulent (2.08) compare to  G. boninense (1.42). Whereas the one which isolated from rubber plant is moderately virulent (0.92). Ganoderma infection was indicated by decreasing the dry weight of infected seedlings. Difference type of isolates did not significantly effect to the decreasing of seedling dry weight 3.82 g (inoculated by G. lucidum), 4.01 g (inoculated by G. boninense), 5.02 g (inoculated by G. applanatum). These results showed that these isolates (especially G. lucidum-like) are species to watch out as for Ganoderma root rot pathogen. The presence of perennials such as palm oil and infected rubber, can be a potential source of inoculum for A. mangium.